Perfectionism, Coping Strategies, and Burnout: A Cross-Sectional Study of Young Competitive Athletes in Indonesia - Elzas Nurajab; Ruslan Rusmana; Sutiswo; Sony Hasmarita; Dafa Fikri Maulana (STKIP Pasundan Press, 2025)
This study aims to examine the relationship between perfectionism, coping strategies, and burnout in competitive young athletes. This research uses a quantitative design with a cross-sectional approach. Participants consisted of 30 young athletes aged 15–19 years; M = 16.8; SD = 1.3, recruited from several Education Centers and PPLP in West Java, with a minimum of three years of competitive training experience. The instruments used were the Athlete Burnout Questionnaire (ABQ), the Sport-Multidimensional Perfectionism Scale 2 (Sport-MPS 2), and the Brief-COPE. Data were analysed using descriptive statistics, Pearson correlation, and hierarchical multiple regression. The research findings indicate that concern over mistakes as a form of maladaptive perfectionism is positively and significantly correlated with all dimensions of burnout. Conversely, personal standards as a form of adaptive perfectionism did not show a significant relationship with burnout and sport devaluation, and had a weak negative correlation with reduced feelings of achievement. Problem-focused coping strategies are negatively correlated with burnout, while emotion/avoidance-focused coping strategies are positively correlated. Regression analysis shows that maladaptive perfectionism is a significant predictor of burnout, with coping strategies playing a role in strengthening or weakening this influence. In conclusion, burnout in young athletes is influenced by the interaction between perfectionistic characteristics and the coping strategies used. These findings confirm the importance of sports psychology interventions that focus on managing maladaptive perfectionism and strengthening adaptive coping strategies in the context of coaching young athletes in Indonesia.